MODERN SOCIETY AND YOUTH ETHICS - Ahamdjanov Olimjon Komiljonovich (Journals Park Publishing, 2025)
This article discusses the various influences of modern electronic media on the morality of young people. It examines the negative impact of mass culture, which undermines our national customs, values, and spirituality, and poisons the minds of our youth.
Keywords: Morality, informatization, virtual world, exchange and reception of information, level of social consciousness, number of users, negative situation, spiritual education of youth, ideological immunity, national interest.